Effect of Marinating Chicken Meat with Lemon, Green Tea and Turmeric Against Foodborne Bacterial Pathogens - Murali, N.; Kumar-Phillips , G.S.; Rath, N.C.; Marcy, J.; Slavik, M.F. (International Journal of Poultry Science, 2012)
Foodborne diseases affect millions of people each year. To reduce the incidence of bacterial foodborne pathogens more effective treatment methods are needed. In this study, we evaluated the effect of marinating chicken breast fillets with extracts of lemon, green tea and turmeric against Campylobacter jejuni and Salmonella enteritidis. The prepared plant extracts in phosphate buffered saline were added to chicken breast fillets both singly and in combination and were incubated at 4°C. Cell counts were made at regular intervals and the viability percentage was calculated. A combination of green tea, lemon and turmeric was found to be the most effective against C. jejuni and S. enteritidis killing all the bacteria within 12 hrs of incubation, with a 5-log reduction in growth within 1 hr of incubation and proved to be more effective than any of the extracts used alone. Further, combinations of both lemon and green tea and lemon and turmeric killed all C. jejuni isolates, but not S. enteritidis, within 24 hrs of incubation. This study showed synergistic effects of lemon, green tea and turmeric extracts as bactericidal agents and that combinations of plant extracts were more effective than using the extracts singly. In summary, it was found that these extracts were effective on chicken meat and should be able to be used as marinates on other meats as well. Since foodborne bacteria are not entirely eliminated using current treatment techniques, plant extracts like lemon, green tea and turmeric could be used as additional treatment options.